Functional State of the Thyroid Gland in Patients with Urticaria - Rudnyk T.; Nadashkevіch O.; Parashchuk B.; Zaychenko Y. (Львівський клінічний вісник)
Introduction. It is known that in 15.0-20.0% of the world’s population there is at least one episode of urticaria throughout the life, and therefore it belongs to the group of dermatoses of a social nature. Significant prevalence, absence of unified diagnostic algorithms, multifactorial etiology, often resistance to treatment and rehabilitation measures with a significant decrease in the quality of life of patients is the cause of a careful attention to its study. However, despite the fact that it would be possible to assume the commonality of the pathogenetic mechanisms of allergic dermatitis and damage to the glands of the internal secretion, in particular, thyroid gland, today the insufficient attention is paid to the research of the role of the latter in the occurrence of urticaria, the information about the informativeness of the individual criteria for assessing its condition, the influence of pathological changes of the thyroid gland on the clinical course of urticaria is not outlined. Aim. To investigate the functional state of the thyroid gland in patients with urticaria and to determine its dependence on the severity of the urticaria, its duration, and the long-term duration of the last clinical remission. Materials and methods. 86 patients with chronic idiopathic urticaria (34 men and 52 women) aged 15-67 years were examined. Control group consisted of 20 healthy people. The duration of the disease varied from 5 months to 29 years. The mild course of dermatosis was diagnosed in 31 (36.0%) patients, the moderate – in 24 (28.0%), and the severe course – in 31 (36.0%). The function of the thyroid gland was evaluated by the determining the level of thyroxin, triiodothyronine and tyroglobulin in the blood serum. Results. In patients with urticaria, there is a dependence of the function of the thyroid gland on the presence and duration of the last remission – significant increase of the thyroxine levels and reduction of triiodothyronine level in the blood serum of patients with the continuous course of urticaria and duration of the last remission up to 3 months, and a possible increase of thyroglobulin level in serum in the patients without remission. Conclusions. It was found that urticaria is accompanied by the dysfunction of the thyroid gland which lies in a certain growth of thyroxine and thyroglobulin and in the reduction of triiodothyronine level in the blood serum. The intensity of the changes mentioned above depends on the clinical course of the pathological process, specifically on the presence and progression of the last clinical remission, in this connection it is expedient to further study the involvement of the thyroid gland into the autoimmune processes in patients with dermatosis.